2014
DOI: 10.1055/s-0034-1382010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antidepressant-like Effect of Olax Subscorpioidea Oliv. (Olacaceae) Extract in Mice

Abstract: Olax subscorpioidea is a shrub or tree found in Nigeria, and other parts of Africa. It is indicated in the management of inflammatory disorder, mental illness, convulsion, pain, and cancer. Based on the folkloric use in the management of mental illness, antidepressant activity of Olax subscorpioidea (6.25?50?mg/kg, i.?p.) was investigated using forced swimming, tail suspension, yohimbine induced lethality and reserpine induced depression tests. The results showed that, Olax subscorpioidea produced significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…Interestingly, in both acetylcholinesterase and butyrylcholinesterase inhibitory activities of ON-Cr, all the concentrations (31.25, 62.50, 125, 250, 500 and 1000 μg/mL) demonstrated % inhibition values not significantly different in comparison to galantamine (standard drug) at the same concentration ( P > 0.05 at 95% confidence interval). Previously, Olax Subscorpioidea is also reported to possess neuroprotective, anxiolytic and anti-depressant properties [ 18 , 21 ]. Significant results noticed in the antioxidant and anticholinesterase assays of ON-Cr may be attributed to the predominant presence of Gallic acid derivatives among the identified compounds (Table 2 ), which is a common poly phenol and strong antioxidant having promising neuroprotective potentials [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in both acetylcholinesterase and butyrylcholinesterase inhibitory activities of ON-Cr, all the concentrations (31.25, 62.50, 125, 250, 500 and 1000 μg/mL) demonstrated % inhibition values not significantly different in comparison to galantamine (standard drug) at the same concentration ( P > 0.05 at 95% confidence interval). Previously, Olax Subscorpioidea is also reported to possess neuroprotective, anxiolytic and anti-depressant properties [ 18 , 21 ]. Significant results noticed in the antioxidant and anticholinesterase assays of ON-Cr may be attributed to the predominant presence of Gallic acid derivatives among the identified compounds (Table 2 ), which is a common poly phenol and strong antioxidant having promising neuroprotective potentials [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse was viewed as stable when it inactively hung with bar without any endeavors to get away. 23 -26…”
Section: Methodsmentioning
confidence: 99%
“…Mouse was viewed as stable when it inactively hung with bar without any endeavors to get away. [23][24][25][26] Acute Toxicity Study of O bracteatum Rules of Organization for Economic Cooperation and Development were pursued to execute acute lethality studies. 27 Mice (22-42 g) were partitioned into 5 different groups, comprising of 5 mice in each group.…”
Section: Evaluation Of Antidepressant Activity Of O Bracteatummentioning
confidence: 99%
“…Previous studies have shown that the plant displayed Antinociceptive [104], anti-ulcer [96], antimicrobial [94] and anti-protease [105] activities. Recently, The Antidepressant effects of the plant were also reported [106]. Olax subscorpioidea leaf possesses hypoglycaemic potential [107] and antifungal activity [108].…”
Section: Fig 10 Olax Subscorpioidea (Oliv)mentioning
confidence: 99%